Factors that affect the quality of sugar cane - Part 1 : climate. - YATES, R.A. (1996)
Defines the effects of climate on cane quality from a review of the literature, and through 'crop-modeling' type analyses based on routine factory reports and agronomic experiments from 15 countries.